Multiple-therapy-resistant-major depressive disorder: a clinically important concept - McAllistair-Williams, R.H.; Christmas, D.M.B.; Cleare, A.J.; Currie, A.; Gledhill, J.; Insole, L.; Malizia, A.L.; McGeever, M.; Morriss, Richard K.; Robinson, Lindsay J.; Scott, M.; Stokes, P.R.A.; et al. (Royal College of Psychiatrists, 2018)
Many novel therapeutic options for depression exist which are either not mentioned in clinical guidelines or recommended only for use in highly specialist services. The challenge faced by clinicians is when it might be appropriate to consider such ‘non-standard’ interventions. This analysis proposes a framework to aid this decision.